Transformasi KKEP Pasca Perpol No. 7 Tahun 2022 Dan Optimalisasi Divisi Propam - nurhaedin, Rafi Dwi Fathurahman Nur (Equality : Jurnal Hukum dan Keadilan, 2025)
The enforcement of the code of ethics within the Indonesian National Police (Polri) still faces significant challenges, such as a high number of violations, lack of transparency, and declining public trust in the police institution. This research aims to analyze the transformation of the role of the Police Code of Ethics Commission (KKEP) following the enactment of Police Regulation Number 7 of 2022 and to examine the optimization of the Professional and Security Division (Propam) in strengthening the internal supervision system of the Indonesian National Police (Polri). The research method used is normative juridical, with data collection through literature study and in-depth interviews with AKP Nurhaedin, Head of Subdivision of Cyber and Information Technology, Subdivision of Professional and Security, Propam Division of Banten Regional Police. The research results show that Perpol No. 7 of 2022 brings significant changes, expanding the authority of KKEP and providing flexibility in determining whether the ethics hearings are open or closed. KKEP now plays a strategic role in building professionalism, transparency, and accountability within the National Police. The optimization of the Propam Division through four oversight systems (internal, external, community, and direct supervision) strengthens the training and enforcement of member discipline. The synergy between KKEP and Propam creates a more effective, fair, and responsive system for enforcing the code of ethics, addressing public criticism, and adapting to technological advancements and social values. This study also recommends strengthening institutional capacity, enhancing coordination with external oversight agencies, as well as community participation and strengthening ethics education within the National Police to build a sustainable culture of professionalism and integrity. These findings are expected to serve as a reference in the future efforts to reform the enforcement of the Polri code of ethics, in order to realize a professional, accountable, and trusted police institution.